Enhancing Fine Motor Skills and Fostering Creativity in Children through Plasticine-Based Activities - Iffah, Nur; Aulina, Choirun Nisak (STAI Hubbulwathan Duri, 2024)
Some children have difficulty developing their creativity and motor skills. Children with fine motor problems may find it difficult to express their creativity. To overcome these problems, the play method using plasticine is one of the alternative solutions. Therefore, this study aims to explore the effect of plasticine play activities on improving fine motor skills and creativity in kindergarten-aged children. This study used a quantitative approach with the type of quasi experiment with a one group pretest posttest research design. This study only involved the experimental group. Data collection in this study used questionnaires in the form of fine motor skills instruments and creative thinking skills in children. This study involved children aged 5-6 years in group B as many as 60 students who were then selected using purposive sampling technique. In this study, the data were analyzed using paired samples t-test. The results showed that there was a significant increase in fine motor skills and creative thinking ability in children after being given treatment using the Plasticine-Based Activities method. This is evidenced by the significance value of 0.001 0.05. However, in this study, it is recommended that kindergarten educators and parents integrate plasticine play activities in the curriculum and daily activities of children. Additional support in the form of training for educators is also needed to maximize the benefits of using plasticine in developing children's skills.